2020
DOI: 10.1136/jech-2019-213666
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid expansion and infant mortality: the (questionable) impact of the Affordable Care Act

Abstract: BackgroundMany states expanded Medicaid eligibility under the Patient Protection and Affordable Care Act (PPACA). Medicaid expansion might impact infant mortality through improved maternal health prior to pregnancy and reduced insurance churn. Some studies suggest the PPACA had no significant impact on low birth weight or preterm birth, while others suggest that the PPACA led to a significant decrease in infant mortality.MethodsUsing a difference-in-differences estimator with fixed effects to control for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Medicaid expansion was associated with improvements in birth outcomes overall. However, in contrast with most of the studies examining the effect of Medicaid expansion on racial disparities [ 25 27 ] and in line with Cook and Stype [ 28 ], we find that Medicaid expansion is associated with better outcomes for White newborns but fail to find a significant relationship between Medicaid expansion and birth outcomes for Black newborns in Texarkana.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Medicaid expansion was associated with improvements in birth outcomes overall. However, in contrast with most of the studies examining the effect of Medicaid expansion on racial disparities [ 25 27 ] and in line with Cook and Stype [ 28 ], we find that Medicaid expansion is associated with better outcomes for White newborns but fail to find a significant relationship between Medicaid expansion and birth outcomes for Black newborns in Texarkana.…”
Section: Discussioncontrasting
confidence: 78%
“…Infant mortality rate decline was greater in Medicaid expansion states, with greater declines among Black infants (in states and Washington, DC) [ 27 ]. However, another study found that infant mortality decreased for babies born to White mothers as a result of Medicaid expansion, but not for babies born to Black mothers [ 28 ]. Therefore, the results seem to be sensitive to sample selection, which makes the external validity of the findings questionable.…”
Section: Introductionmentioning
confidence: 99%
“…The fact mothers without insurance consistently had the highest mortality rates may reflect their underlying SES. Ensuring all mothers have appropriate insurance is important; however, previous studies have debated the effect of the expansion of Medicaid on infant mortality …”
Section: Discussionmentioning
confidence: 99%